Work-Life Balance dan Pengaruhnya terhadap Prestasi Akademik: Studi Kasus pada Mahasiswa Universitas Terbuka dengan Pekerjaan Paruh Waktu - Muchammad Wildan Alkautsar; Imroatul Fatehah; Dina Noval Madurani (Universitas Syiah Kuala, 2025)
This study aims to examine the effect of work-life balance (WLB) on academic achievement in the University of Terbuka who work part-time. Work-Life Balance or the balance between life on work is an important global issue, especially among students who have a two activity, namely study and work part-time. This study employed a quantitative approach with a survey method, where data was obtained by distributing questionnaires to 150 respondents selected using purposive sampling techniques. Data analysis was performed using descriptive statistics and linear regression, processed using SPSS version 27 for windows. The results of the validity and reliability tests indicate that all research instruments are valid and reliable. Work-Life Balance shows a significance value of 0.001 with an Unstandardized Beta value of 0.164, which indicates a positive influence on the students' academic achievement. These results support the research hypothesis that students' work-life balance plays a significant role in determining their academic achievement. The implications of this study highlight the importance of WLB for part-time students in achieving optimal academic achievement and provide recommendations for students, educational institutions, and organizations to support work-life balance.